(Im)mobility and performance of emotions: Chinese international students' difficult journeys to home during the COVID-19 pandemic. (May 2023) - He, Guanqin; Zhang, Yijia
This article examines mediated performances of emotions by Chinese international students in their transnational journeys returning to China during the COVID-19 pandemic with a focus on the role of mobile media in helping students cope with their cross-border (im)mobility and symbolic immobility. By thematically analyzing 36 self-representational videos produced by returning Chinese students on a burgeoning mobile media platform Douyin, we identify 5 overarching themes of emotional performance: fear, pride, gratitude, shame, and solidarity. We propose that mobile media has the potential to create a hybrid space that witnesses and elicits empathy for the hardship experienced by marginalized mobile groups during the global pandemic. Mobile media, by enabling simultaneous communication, amplifies the sensation of belonging in times of isolation and ambiguity and offers dialogic venues for disparate groups across geographical and socioemotional distances. Our findings suggest the vulnerability of mobile communities in the event of a global pandemic, and the affordances of mobile media in confronting and resolving such precarity. We call attention to the intersections of mobile communities and mobile media amid the global pandemic, particularlyon the experiences and performances of emotions in hybrid spaces.